Comparison of treatment persistence, adherence, and risk of exacerbation in patients with COPD treated with single-inhaler versus multiple-inhaler triple therapy: A prospective observational study in China - Lin, Ling; Liu, Cong; Cheng, Wei; Song, Qing; Zeng, Yuqin; Li, Xin; Deng, Dingding; Liu, Dan; Chen, Yan; Cai, Shan; Chen, Ping (Frontiers in Pharmacology, 2023)
Purpose: Compare treatment persistence, adherence and risk of exacerbation among patients with COPD treated with SITT and MITT in Chinese population. Methods: This was a multicentric and prospective observation study. Patients with COPD of 10 hospitals in Hunan and Guangxi province in China from 1 January 2020 to 31 November 2021 were recruited into the study and followed up for one year. Persistence, adherence and exacerbation rates during 12 months follow-up were analyzed in patients treated with SITT and MITT in COPD. Results: A total of 1328 patients were enrolled for final analysis, including 535 (40.3%) patients with SITT and 793(59.7%) patients with MITT. Of all patients, the mean age of patients was 64.9 years old and most patients were male. The mean CAT score was 15.2 ± 7.1, the median (IQR) FEV1% was 54.4 (31.2). SITT group had higher mean CAT score, higher mean CCQ score, more patients with mMRC >1 and lower mean FEV1 % and FEV1/FVC than MITT group. Moreover, the proportion of patients with ≥1 exacerbation was higher in SITT cohort. SITT patients had higher proportion of adherence (proportion of days covered, PDC)≥0.8 (86.5% vs79.8%; P=0.006), higher treatment persistence [HR:1.676(1.356-2.071), P<0.001], lower risk of moderate-to severe exacerbation [HR:0.729(0.593-0.898), P=0.003] and severe exacerbation [HR:0.675(0.515-0.875), P=0.003] during 12 months follow up. For both SITT and MITT, persistence was associated with improved future exacerbation rates versus non-persistence. Conclusions: Patients with COPD treated with SITT had an improvement in treatment persistence and adherence, as well as risk reduction of moderate-to severe exacerbation and severe exacerbation compared with patients with MITT in Chinese population.